Problems associated with the storage of citrus fruits - Ahmad A.M.M. Al-Salem (1984)
The effect of post-harvest coating of oranges (Citrus sinensis) and grapefruit (C. paradisi) with Pro-long at different concentrations was investigated under three different storage conditions: cold ambient, tropical ambient and cold store conditions. There was a definite advantage in storing fruits at low temperature using Pro-long in terms of shelf-life extension and reducing weight loss. Thiabendazole was found to be effective in controlling citrus decay during storage when used at concentration of 1000 ppm. [Continues.]